(3eNGWQ GdGSJKeGQ aj GdeUGQa GdESdGejI (B/s - (3MeGO, MeRI YHO GdcQje eMeOs ((3YeGf, GdCQOf (B:s (3OGQ GdfaGFS ddfTQ hGdJhRjY ,s, 2008)
(3aj Gdabg hCUhdg(B.s
(3ZdGa eUhQ(B.s
(3jTJed Ydi cTGa(B.s
(3GdCUd CWQhMI OcJhQGg(B-(3cdjI GdTQjYI, GdLGeYI GdCQOfjI(B.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
(3HHdjhLQGajI (B: (3UaMI (B217-241.s
(3jTJed Ydi edNU HGddZI GdEfLdjRjI(B.s
Keywords: (3GdHfhc GdESdGejIs; (3GdGSJKeGQ (B((3GbJUGO ESdGej(B)s